Phosphodiesterase type 5 inhibitor to riociguat transition is associated with hemodynamic and symptomatic improvement in pulmonary hypertension - Davey, Ryan (Pulm Circ, 2017)
Riociguat is a soluble guanylate cyclase stimulator approved for the treatment of pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension. We studied the clinical and hemodynamics effects of transitioning 12 pulmonary hypertension patients from Phosphodiesterase type 5 inhibitor (PDE5i) to riociguat, and demonstrated a significant increase in cardiac index, fall in pulmonary vascular resistance, and improvement in functional class with this switch. Switch from PDE5i to riociguat appeared to be safe and fairly well tolerated in most patients.